Zapomniane dywizjony : losy lotnikow polskich - Zamoyski, Adam. (London : Puls, 1995)
An account of the Polish Air Force which fought with the British during WW II.
Includes bibliographical references p. [257]-263.
Keywords: World War, 1939-1945 -- Aerial operations, Polish; Poland. -- Polskie Sily Powietrzne; Poland. -- Lotnicze Sily Zbrojne